Composite material, method for producing the same, electrode, and battery

CN123017915APending Publication Date: 2026-10-30HUNAN SHINZOOM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611014620.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-08
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0003]相关技术中,通常在石墨表面进行改性包覆以提高其性能,然而,现有的包覆方法难以进行均匀有效包覆,对石墨的改性有限,包覆方法仍有待进一步改善

Benefits of technology

[0029]本申请先提供腈类聚合物预包覆石墨的预包覆物,再采用气相沉积引入硫源制备复合材料,在气相反应的均匀性、结构完整性保护、及形成高浓度Li+环境等方面具有显著的优势:在真空气相沉积条件下,升华硫源以气态形式存在,能够通过分子扩散方式均匀渗透到石墨颗粒的各个表面,克服了固相球磨混合的不均匀性;通过精确控制气相沉积中硫源的升华温度、反应温度、真空度和反应时间,可以精确调控含硫腈类聚合物包覆层的厚度和硫含量,实现界面浓度梯度的优化设计;真空条件下的气相反应避免了机械球磨对石墨结构的破坏,保留了石墨的完整晶格结构,有利于锂离子的快速扩散;均匀致密的含硫腈类聚合物包覆层能够在锂化后形成更加陡峭的浓度梯度,更有效地驱动Li+向石墨内部扩散,从而显著提升倍率性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017915A_ABST
    Figure CN123017915A_ABST
Patent Text Reader

Abstract

The application discloses a composite material and a preparation method thereof, an electrode and a battery, and relates to the technical field of new energy. The preparation method of the composite material comprises the following steps: providing a pre-coated material, wherein the pre-coated material comprises graphite and a nitrile polymer coating the graphite; and providing a sulfur source, and reacting and combining the pre-coated material through gas phase deposition to obtain the composite material. According to the application, the pre-coated material of the nitrile polymer pre-coating the graphite is provided first, and then the sulfur source is introduced through gas phase deposition to prepare the composite material, so that the uniformity of the gas phase reaction, the structural integrity protection and the formation of high-concentration Li + The application has significant advantages in the aspects of environment and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of new energy technology, and in particular to a composite material and its preparation method, electrode and battery. Background Technology

[0002] Graphite is an allotrope of carbon, possessing a typical layered hexagonal crystal structure. Carbon atoms, hybridized in sp², form a planar hexagonal grid stacked along the c-axis, with weak van der Waals forces binding the layers together. This structure endows it with excellent electronic conductivity, thermal conductivity, chemical stability, and intercalation capability. In the battery field, graphite is currently the most mainstream anode material for commercial lithium-ion batteries. Its layered structure allows for reversible lithium-ion insertion and extraction, offering advantages such as high specific capacity, low lithium intercalation potential, good cycle stability, and low cost. It is widely used in consumer electronics, power batteries, and energy storage batteries.

[0003] In related technologies, graphite surfaces are typically modified and coated to improve their properties. However, existing coating methods are difficult to achieve uniform and effective coating, and the modification of graphite is limited. The coating methods still need further improvement. Summary of the Invention

[0004] In view of this, this application provides a composite material, a method for preparing the same, an electrode, and a battery.

[0005] The embodiments of this application are implemented as follows: Firstly, the embodiments of this application provide a method for preparing a composite material, comprising the following steps: A pre-coating material is provided, the pre-coating material comprising graphite and a nitrile polymer coating the graphite; A sulfur source is provided, and the sulfur is reacted with the pre-coated material via vapor deposition to obtain a composite material.

[0006] Optionally, in some embodiments of this application, the average particle size D of the graphite is... v 50 ranges from 4μm to 20μm.

[0007] The nitrile polymers include polyacrylonitrile, polymethacrylonitrile, polybutene nitrile, polypentene nitrile, polyhexene nitrile, polystyrene-acrylonitrile copolymer, acrylonitrile-butadiene-styrene copolymer, acrylonitrile-butadiene copolymer, hydrogenated acrylonitrile-butadiene rubber, acrylonitrile-styrene-acrylate copolymer, acrylonitrile-chlorinated polyethylene-styrene copolymer, acrylonitrile-methyl methacrylate copolymer, acrylonitrile-acrylate copolymer, acrylonitrile-vinylpyridine copolymer, acrylonitrile-vinyl chloride copolymer, acrylonitrile-vinylidene chloride copolymer, acrylonitrile-maleic anhydride copolymer, and acrylonitrile-acrylamide copolymer.

[0008] The mass ratio of the graphite to the nitrile polymer is 100:(0.2~3).

[0009] The average thickness of the pre-coated layer formed by the nitrile polymer coating the graphite is 5 nm to 15 nm.

[0010] Optionally, in some embodiments of this application, the method for preparing the pre-coated material includes: providing the graphite, the nitrile polymer and a solvent, mixing and kneading them to obtain the pre-coated material.

[0011] The solvent includes one or more of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, N-ethylpyrrolidone, N-cyclohexylpyrrolidone, N-octylpyrrolidone, γ-butyrolactone, propylene carbonate, ethylene carbonate, sulfolane, 1,3-dimethyl-2-imidazolinone, hexamethylphosphoric triamine, tetrahydrofuran, dioxane, acetonitrile, acetone, and methyl ethyl ketone.

[0012] Following the kneading process, the method further includes drying to remove the solvent. The method for drying to remove the solvent includes heating. The heating temperature is 60°C to 100°C.

[0013] Optionally, in some embodiments of this application, the sulfur source includes one or more of elemental sulfur and metal sulfides, wherein the metal sulfide includes MoS₂. x x is any integer from 1 to 5.

[0014] The mass ratio of the nitrile polymer to the sulfur source is 10:(1~8).

[0015] Optionally, in some embodiments of this application, the vacuum degree of the vapor deposition is ≤500Pa.

[0016] The heating rate for vapor deposition is 1℃ / min to 10℃ / min.

[0017] The temperature for vapor deposition is 300℃~600℃.

[0018] The vapor deposition time is 1h to 8h.

[0019] Optionally, in some embodiments of this application, the vacuum degree of the vapor deposition is ≤200Pa.

[0020] The heating rate for the vapor deposition is 2℃ / min to 8℃ / min.

[0021] The temperature for vapor deposition is 300℃~400℃.

[0022] The vapor deposition time is 2h to 4h.

[0023] Optionally, in some embodiments of this application, the composite material includes the graphite and a coating layer covering the graphite.

[0024] The coating material includes a thionitrile polymer.

[0025] The average thickness of the coating layer is 3nm to 10nm.

[0026] Secondly, embodiments of this application also provide a composite material prepared by the above-described preparation method.

[0027] Thirdly, embodiments of this application also provide an electrode, the material of which includes the composite material prepared by the above-described preparation method, or includes the above-described composite material.

[0028] Fourthly, embodiments of this application also provide a battery, the battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the material of the negative electrode comprises a composite material prepared by the above-described preparation method, or comprises the above-described composite material, or the negative electrode comprises the above-described electrode.

[0029] This application first provides a pre-coated graphite material pre-coated with a nitrile polymer, and then uses vapor deposition to introduce a sulfur source to prepare a composite material. This addresses the issues of uniformity in the vapor-phase reaction, protection of structural integrity, and the formation of a high-concentration Li. + It offers significant advantages in terms of environment and other aspects: Under vacuum vapor deposition conditions, the sublimated sulfur source exists in gaseous form and can uniformly penetrate to all surfaces of graphite particles through molecular diffusion, overcoming the inhomogeneity of solid-phase ball milling; by precisely controlling the sublimation temperature, reaction temperature, vacuum degree, and reaction time of the sulfur source in vapor deposition, the thickness and sulfur content of the sulfur-containing nitrile polymer coating layer can be precisely controlled, achieving optimized design of the interface concentration gradient; the vapor-phase reaction under vacuum conditions avoids the damage to the graphite structure caused by mechanical ball milling, preserving the complete lattice structure of graphite, which is conducive to the rapid diffusion of lithium ions; the uniform and dense sulfur-containing nitrile polymer coating layer can form a steeper concentration gradient after lithiation, more effectively driving Li-ion diffusion. + It diffuses into the interior of graphite, thereby significantly improving rate performance. Attached Figure Description

[0030] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0031] Figure 1 This is a flowchart illustrating a method for preparing a composite material according to an embodiment of this application; Figure 2 This is a SEM microstructure image of the composite material provided in Example 1 of this application; Figure 3 This is the S2p XPS spectrum of the coating layer in the composite material provided in Example 1 of this application. Detailed Implementation

[0032] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application. Furthermore, it should be understood that the specific embodiments described herein are only for illustration and explanation of this application and are not intended to limit this application.

[0033] In this application, unless otherwise stated, directional terms such as "upper" and "lower" generally refer to the upper and lower positions of the device in its actual use or operating state, specifically the orientation shown in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. Furthermore, in the description of this application, the term "comprising" means "including but not limited to". The terms first, second, third, etc., are used merely as illustrative purposes and do not impose numerical requirements or establish a numerical order.

[0034] In this application, "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural.

[0035] In this application, "at least one" means one or more, and "more than one" means two or more. "One or more", "at least one of the following", or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.

[0036] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.

[0037] In this application, the term "numerical interval" (i.e., numerical range) is used. Unless otherwise specified, the distribution of selectable numerical values ​​within the numerical interval is considered continuous, and includes the two endpoints (i.e., the minimum and maximum values) of the numerical interval, as well as every value between these two endpoints. Unless otherwise specified, when the numerical interval refers only to integers within the numerical interval, it includes the two endpoint integers of the numerical range, as well as every integer between the two endpoints, which is equivalent to directly listing every integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be merged. In other words, unless otherwise specified, the numerical range disclosed herein should be understood to include any and all subranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, percentage, ratio, etc. The term "numerical interval" can be broadly included to include numerical interval types such as percentage intervals, ratio intervals, and proportion intervals.

[0038] Unless otherwise specified, the temperature parameters in this application may be either constant temperature treatment or variations within a certain temperature range. It should be understood that the constant temperature treatment allows temperature fluctuations within the precision range of the instrument control, such as ±5℃, ±4℃, ±3℃, ±2℃, or ±1℃.

[0039] With the increasing demand for energy density in lithium-ion batteries, graphite anodes face three main challenges at high rates: First, capacity and rate performance are limited. Graphite's theoretical specific capacity is only 372 mAh / g. At high rates, the surface lithium intercalation rate far exceeds the interlayer diffusion rate, leading to lithium ion accumulation on the surface and a kinetic mismatch, becoming a key bottleneck for improving rate performance. Second, lithium plating poses safety and lifespan risks. When the surface lithium concentration exceeds the lithium intercalation limit, metallic lithium precipitates in dendrite form, resulting in irreversible loss of active lithium, continuous electrolyte consumption, SEI thickening, and increased impedance. Furthermore, dendrites may puncture the separator, causing a short circuit. Third, existing modification technologies cannot fundamentally solve the problem: electrolyte additives only optimize the SEI and are unlikely to improve bulk diffusion; ALD / CVD artificial SEIs are costly and increase impedance; carbon coating offers limited improvement in kinetics; nano-sizing reduces tap density; and pre-lithiation only mitigates the consequences without eliminating the root cause of lithium plating.

[0040] To address the aforementioned challenges, related technologies often involve constructing an in-situ coating layer on the graphite surface to improve its performance. However, existing methods for preparing coated graphite often employ simple physical coating and mixing techniques, resulting in the coating layer easily detaching during battery cycling. Furthermore, relying solely on mechanical contact makes it difficult to form a continuous coating layer, leaving a large amount of graphite surface exposed, increasing interfacial impedance, and requiring additional interfacial barriers to overcome for lithium-ion transport.

[0041] In summary, while existing technologies attempt to address the lithium plating problem in graphite, they have failed to achieve the two key technical objectives of chemical bonding and molecular-level uniform coating of the coating layer on the graphite surface. Therefore, there is an urgent need in this field for a preparation method that can achieve uniform and robust coating while protecting the structural integrity of graphite.

[0042] The technical solution of this application is as follows: Firstly, please refer to Figure 1 This application provides a method for preparing a composite material, comprising the following steps: Step S11: Provide a pre-coating material, the pre-coating material comprising graphite and a nitrile polymer coating the graphite; Step S12: Provide a sulfur source, and react it with the pre-coated material via vapor deposition to obtain a composite material.

[0043] The composite material includes the graphite and a coating layer covering the graphite. The coating layer is made of a thiocyanate-containing polymer.

[0044] It should be noted that the nitrile polymers refer to organic polymers whose main chain or side chain structure contains cyano groups (-CN). Correspondingly, the sulfur-containing nitrile polymers refer to organic polymeric materials in which sulfur is introduced into the nitrile polymer.

[0045] It should also be noted that vapor deposition refers to a material processing method in which one or more gaseous precursors are introduced into a reaction system under certain temperature, pressure, and atmospheric conditions, causing them to adsorb, decompose, react, or deposit on the surface of a substrate material, thereby forming a target deposition layer, modified layer, or doped structure on the substrate surface. Specifically, vapor deposition in this application refers to the process of forming gaseous sulfur-containing reactive species from a sulfur source in a vacuum environment under vapor deposition conditions, and then reacting with the surface of the pre-coated material through a deposition or sulfidation reaction to form a sulfur-containing modified structure on and / or inside the pre-coated material.

[0046] The method for preparing the composite material provided in this application utilizes the high volatility of sublimated sulfur source under vacuum conditions to allow gaseous sulfur molecules to fully diffuse and uniformly contact the surface of graphite particles pre-coated with nitrile polymers, forming a continuous and dense sulfur-containing nitrile polymer coating layer through in-situ thermal reaction. Compared with the prior art, this invention has the following key differences and advantages: In terms of reaction mechanism, existing ball milling and spray drying methods involve mixing solid or liquid phases before heat treatment. The sulfur-containing nitrile polymers are generated far from the graphite surface before contacting the graphite, or the nitrile polymers react with the sulfur source outside the graphite before adhering to the graphite surface. In contrast, this application first uniformly coats the graphite surface with nitrile polymers as a reaction substrate, and then introduces gaseous sulfur, so that the sulfurization reaction occurs directly in the nitrile polymer layer on the graphite surface, achieving in-situ growth of sulfur-containing nitrile polymers on the graphite surface. This difference determines the bonding mode between sulfur-containing nitrile polymers and graphite: in the prior art, the two are in physical contact, while in this application, the graphite core and the sulfur-containing nitrile polymer are covalently bonded through CSSC chemical bonds, making the coating layer less prone to detachment during cycling. Furthermore, this application does not perform heat treatment before the sulfur source is vapor-deposited on the pre-coated material. This is to avoid cross-linking of the nitrile polymer, which would occupy the reaction sites of the sulfur source and lead to a significant reduction in the number of CS bonds in the final sulfur-containing nitrile polymer. This application uses vacuum chemical vapor deposition, which allows cyclization and sulfidation to proceed simultaneously. Sulfur can participate in the reaction more effectively, forming a higher content of CS bonds. The final product has high utilization rate of active materials and large reversible capacity. If the nitrile polymer is pre-treated by cyclization, the nitrile polymer molecular chain will condense and cyclize in advance, which will consume the reaction sites on the main chain that can bond with sulfur. At the same time, the cyclization and cross-linking structure will hinder the uniform diffusion of subsequent sulfur vapor into the interior of the coating layer, resulting in uneven distribution of sulfur in the coating layer and reduced CS bond formation efficiency.

[0047] Regarding coating uniformity, existing ball milling and pre-formed sulfur-containing nitrile polymer blending methods rely on macroscopic stirring to achieve material mixing, making it difficult to ensure that each graphite particle surface receives a coating layer of the same thickness. Although spray drying achieves droplet-scale mixing, the distribution of nitrile polymers within the droplets exhibits a concentration gradient, resulting in an uneven coating layer after drying. This application utilizes the molecular diffusion characteristics of a gaseous sulfur source, allowing sulfur vapor to penetrate indiscriminately to every surface of each graphite particle like a gas, reacting with the nitrile polymer at the molecular scale. The resulting sulfur-containing nitrile polymer coating layer is continuous, dense, and of uniform thickness.

[0048] In protecting the graphite structure, the mechanical force of ball milling directly damages the graphite lattice, and the high-temperature sintering after spray drying can also easily cause thermal stress damage to the graphite. This application is carried out under vacuum conditions, at a lower reaction temperature (specifically lower than the conventional sintering temperature), and without any external mechanical force throughout the process, thus preserving the complete lattice structure of the graphite, which is crucial for the rapid diffusion of lithium ions.

[0049] In terms of environmental friendliness, spray drying requires the use of large amounts of toxic organic solvents such as NMP and DMF, resulting in high solvent recovery costs and environmental pressure. Although this application also uses a small amount of solvent in the nitrile polymer coating stage, the subsequent vulcanization reaction is carried out by vapor phase deposition, which is carried out entirely under solvent-free gas phase conditions. Furthermore, the amount of sulfur used can be precisely controlled, and the burden of exhaust gas treatment is relatively light.

[0050] In summary, this application first provides a nitrile polymer pre-coated graphite pre-coating, and then uses vapor deposition to introduce a sulfur source to prepare a composite material. This approach improves the uniformity of the vapor-phase reaction, protects structural integrity, and forms a high concentration of Li. + It offers significant advantages in terms of environment and other aspects: Under vacuum vapor deposition conditions, the sublimated sulfur source exists in gaseous form and can uniformly penetrate to all surfaces of graphite particles through molecular diffusion, overcoming the inhomogeneity of solid-phase ball milling; by precisely controlling the sublimation temperature, reaction temperature, vacuum degree, and reaction time of the sulfur source in vapor deposition, the thickness and sulfur content of the sulfur-containing nitrile polymer coating layer can be precisely controlled, achieving optimized design of the interface concentration gradient; the vapor-phase reaction under vacuum conditions avoids the damage to the graphite structure caused by mechanical ball milling, preserving the complete lattice structure of graphite, which is conducive to the rapid diffusion of lithium ions; the uniform and dense sulfur-containing nitrile polymer coating layer can form a steeper concentration gradient after lithiation, more effectively driving Li-ion diffusion. + It diffuses into the interior of graphite, thereby significantly improving rate performance.

[0051] In step S11: In some embodiments, the average particle size D of the graphite v The particle size of graphite is 4μm to 20μm, for example, it can be 4μm, 5μm, 8μm, 10μm, 12μm, 15μm, 18μm, 20μm, or any range between two of the above values. The graphite has a suitable particle size and exhibits excellent electrical and thermal conductivity. In this application, the particle size of the graphite can be obtained by laser particle size analysis.

[0052] In some embodiments, the nitrile polymers include polyacrylonitrile (PAN), polymethacrylonitrile (PMAN), polybutadiene nitrile (PBN), polypentadiene nitrile, polyhexadiene nitrile, polystyrene-acrylonitrile copolymer (SAN), acrylonitrile-butadiene-styrene copolymer (ABS), acrylonitrile-butadiene copolymer (NBR), hydrogenated acrylonitrile-butadiene rubber (HNBR), acrylonitrile-styrene-acrylate copolymer (ASA), acrylonitrile-chlorinated polyethylene-styrene copolymer (ACS), acrylonitrile-methyl methacrylate copolymer, acrylonitrile-acrylate copolymer, acrylonitrile-vinylpyridine copolymer, acrylonitrile-vinyl chloride copolymer, acrylonitrile-vinylidene chloride copolymer, acrylonitrile-maleic anhydride copolymer, and acrylonitrile-acrylamide copolymer.

[0053] In some embodiments, the method for preparing the pre-coated material includes: providing the graphite, the nitrile polymer, and a solvent, mixing and kneading them to obtain the pre-coated material. Mixing the graphite and nitrile polymer in a liquid solvent environment facilitates uniform contact, resulting in a uniform and dense pre-coated layer formed by the nitrile polymer.

[0054] It should be noted that kneading refers to the process of placing materials such as powders, granules, binders, solvents, and additives in equipment with shearing, extrusion, tumbling, or kneading functions, and subjecting them to forced mixing and plasticizing dispersion under certain temperature, rotation speed, and time conditions, so that the components are fully contacted, uniformly distributed, and form a structure with certain adhesiveness, plasticity, or agglomeration. In the field of materials preparation, kneading is not only simple mixing, but also usually involves wetting, dispersion, bonding, coating, penetration, agglomeration, or preliminary plasticization. In this application, kneading specifically refers to the process of fully dispersing nitrile polymers onto the surface of graphite particles in a liquid solvent environment for preliminary uniform coating.

[0055] In some embodiments, the solvent includes one or more of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), dimethyl sulfoxide (DMSO), N-ethylpyrrolidone (NEP), N-cyclohexylpyrrolidone (CHP), N-octylpyrrolidone (NOP), γ-butyrolactone (GBL), propylene carbonate (PC), ethylene carbonate (EC), sulfolane, 1,3-dimethyl-2-imidazolinone (DMI), hexamethylphosphoric triamine (HMPA), tetrahydrofuran (THF), 1,4-dioxane, acetonitrile (ACN), acetone, and methyl ethyl ketone (MEK).

[0056] In some embodiments, the mass fraction of the nitrile polymer in the solvent is 0.1% to 10%, for example, it can be 0.1%, 0.5%, 1%, 3%, 5%, 7%, 9%, 10%, or any range between two of the above values. Within this mass fraction range, uniform dissolution and dispersion of the nitrile polymer is beneficial. It should be noted that the mass fraction of the nitrile polymer in the solvent refers to the mass of the nitrile polymer divided by the sum of the masses of the nitrile polymer and the solvent.

[0057] In some embodiments, the mass ratio of graphite to the nitrile polymer is 100:(0.2~3), for example, it can be 100:0.2, 100:0.5, 100:1, 100:2, 100:3, or any range between two of the above ratios. Within the range of the mass ratio, it is beneficial for the nitrile polymer to achieve an appropriate amount of coating, thereby improving the migration rate of lithium ions.

[0058] In some embodiments, the kneading speed is 10 rpm to 100 rpm, for example, 10 rpm, 20 rpm, 50 rpm, 80 rpm, 100 rpm, or any range between two of the above values; the kneading time is 1 hour to 10 hours, for example, 1 hour, 2 hours, 5 hours, 8 hours, 10 hours, or any range between two of the above values. Thus, under these kneading conditions, it is beneficial for the nitrile polymer to uniformly coat the surface of the graphite particles, achieving pre-coating, and the kneading has low mechanical strength, which can achieve uniform mixing while avoiding damage to the graphite lattice.

[0059] In some embodiments, after the kneading process, the method further includes drying to remove the solvent. The drying to remove the solvent can employ conventional methods in the art, such as vacuum drying, heat drying, or reduced pressure drying. Further, the heat drying temperature can be 60°C to 100°C to remove the solvent as thoroughly as possible without causing decomposition of the nitrile polymer.

[0060] In some embodiments, the average thickness of the pre-coating layer formed by the nitrile polymer coating the graphite is 5 nm to 15 nm, for example, it can be 5 nm, 8 nm, 10 nm, 12 nm, 15 nm, or any two of the above values. Within this range of average thickness, it is beneficial for the nitrile polymer to perform initial coating and positioning, facilitating the formation of a coating layer of suitable thickness after the subsequent introduction of a sulfur source.

[0061] In step S12: In some embodiments, the sulfur source includes one or more of elemental sulfur and metal sulfides.

[0062] Furthermore, the elemental sulfur may include S8.

[0063] The metal sulfide may include MoS₂. x (Molybdenum sulfide), where x is any integer from 1 to 5. Specifically, MoS x It can be molybdenum monosulfide, molybdenum disulfide, molybdenum trisulfide, etc. When the sulfur source contains other elements besides sulfur, such as Mo, Mo may also remain in the coating layer and play a positive catalytic role.

[0064] It is understood that the vapor deposition is performed under vacuum conditions.

[0065] In some embodiments, the mass ratio of the nitrile polymer to the sulfur source is 10:(1~8), for example, it can be 10:1, 10:2, 10:3, 10:4, 10:5, 10:6, 10:7, 10:8, or any range between two of the above ratios. Within the range of the mass ratio, it is beneficial for the nitrile polymer and the sulfur source to undergo a sufficiently uniform reaction.

[0066] In some embodiments, the vacuum degree of the vapor deposition is ≤500Pa, for example, it can be 100Pa, 200Pa, 300Pa, 400Pa, 500Pa or any two of the above values; the heating rate of the vapor deposition is 1℃ / min to 10℃ / min, for example, it can be 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min or any two of the above values; the temperature of the vapor deposition is 300℃ to 600℃, for example, it can be 300℃, 320℃, 350℃, 380℃, 400℃, 500℃, 600℃ or any two of the above values; the vapor deposition time is 1h to 8h, for example, it can be 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h or any two of the above values. Furthermore, the vacuum degree of the vapor deposition is ≤200 Pa; the heating rate of the vapor deposition is 2℃ / min~8℃ / min; the temperature of the vapor deposition is 300℃~400℃; and the time of the vapor deposition is 2h~4h. Thus, under the conditions of vapor deposition, the sulfur source sublimates upon heating into gaseous sulfur. The sulfur vapor diffuses into the pre-coated material and undergoes a vulcanization reaction with the nitrile polymer on the graphite surface, generating a sulfur-containing nitrile polymer coating layer in situ. After the reaction is completed, the material is allowed to cool naturally. Nitrogen is then introduced into the reaction vessel to replace the residual gas. The replacement tail gas is discharged into a tail gas treatment device, and the composite material is obtained upon discharge.

[0067] In some embodiments, the average thickness of the coating layer is 3 nm to 10 nm, for example, it can be 3 nm, 4 nm, 5 nm, 6 nm, 8 nm, 10 nm, or any range between two of the above values. Within the range of the average thickness of the coating layer, after effective lithiation, the coating layer can establish a steep concentration gradient between the graphite "surface-bulk phase," continuously driving lithium ions to diffuse rapidly into the graphite interior. It should be noted that nitrile polymers undergo a series of structural changes during heating and vulcanization, which lead to volume shrinkage and a reduction in the coating layer thickness. In this application, the average thickness of the coating layer can be obtained by scanning electron microscopy (SEM).

[0068] It should be noted that the composite material can be a single graphite particle with a coating layer on its surface, or multiple graphite particles can be coated with a single coating layer, which can be selected according to actual needs.

[0069] Secondly, embodiments of this application also provide a composite material prepared by the above-described preparation method.

[0070] It is understood that the composite material includes the graphite and a coating layer covering the graphite. The coating layer is made of the sulfur-containing nitrile polymer.

[0071] Thirdly, embodiments of this application also provide an electrode, the material of which includes the composite material prepared by the above-described preparation method, or includes the above-described composite material.

[0072] Fourthly, embodiments of this application also provide a battery, the battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the material of the negative electrode comprises a composite material prepared by the above-described preparation method, or comprises the above-described composite material, or the negative electrode comprises the above-described electrode.

[0073] The positive electrode, separator, and electrolyte can be made of conventional materials in this field, and will not be described in detail here.

[0074] The composite material prepared by the preparation method provided in this application can be used as the negative electrode of a battery to effectively improve battery capacity, charge-discharge performance and rate performance. The cross-linked network structure of the coating layer can also improve the high-temperature storage performance of the battery.

[0075] The present application will be specifically described below through specific embodiments. The following embodiments are only some embodiments of the present application and are not intended to limit the present application.

[0076] Composite Material Example 1 This embodiment of the composite material provides a composite material, and the preparation method of the composite material includes the following steps: Step S21: Add 10g of nitrile polymer polyacrylonitrile to 300g of NMP solvent, stir to fully dissolve the polyacrylonitrile, and form a uniform slurry; add 1kg of graphite (average particle size D) to a mixing pot. v 50 (12μm), then add the prepared polyacrylonitrile slurry into a kneading pot and knead at 20 rpm for 2 hours; then heat to 80℃ to dry and remove solvent to obtain the pre-coated polyacrylonitrile graphite. Step S22: The pre-coated material is mixed uniformly with 5g of elemental sulfur (S8, the mass ratio of polyacrylonitrile to elemental sulfur is 2:1) using a mixer. The mixture is then placed into a CVD reactor. The reactor is evacuated to 10Pa, and the temperature is raised to 350℃ at a heating rate of 4℃ / min. The reaction is maintained at this temperature for 6 hours to generate a sulfur-containing nitrile polymer coating layer in situ. After the reaction is completed, the mixture is allowed to cool naturally. Nitrogen gas is then introduced into the reactor to replace the residual gas. The replacement tail gas is discharged into a tail gas treatment device, and the finished product is the composite material. The composite material includes the graphite and a sulfur-containing nitrile polymer coating layer (average thickness of 6nm) covering the graphite.

[0077] Composite Material Example 2 This composite material embodiment is basically the same as composite material embodiment 1, except that the nitrile polymer in step S21 is replaced with acrylonitrile-chlorinated polyethylene-styrene copolymer in this composite material embodiment.

[0078] Composite Material Example 3 This composite material embodiment is basically the same as composite material embodiment 1, except that the sulfur source in step S22 is replaced with molybdenum disulfide in this composite material embodiment.

[0079] Composite Material Example 4 This composite material embodiment is basically the same as Composite Material Embodiment 1, except that in step S21 of this composite material embodiment, the mass of polyacrylonitrile is 30g and the mass ratio of graphite to polyacrylonitrile is 100:3; in step S22, the mass of elemental sulfur is 15g and the mass ratio of polyacrylonitrile to elemental sulfur is 2:1.

[0080] Composite Material Example 5 This composite material embodiment is basically the same as Composite Material Embodiment 1, except that in step S21 of this composite material embodiment, the mass of polyacrylonitrile is 2g and the mass ratio of graphite to polyacrylonitrile is 100:0.2; in step S22, the mass of elemental sulfur is 1g and the mass ratio of polyacrylonitrile to elemental sulfur is 2:1.

[0081] Composite Material Example 6 This composite material embodiment is basically the same as composite material embodiment 1, except that in step S22 of this composite material embodiment, the mass of elemental sulfur is 8g, and the mass ratio of polyacrylonitrile to elemental sulfur is 5:4.

[0082] Composite Material Example 7 This composite material embodiment is basically the same as composite material embodiment 1, except that in step S22 of this composite material embodiment, the mass of elemental sulfur is 1g, and the mass ratio of polyacrylonitrile to elemental sulfur is 10:1.

[0083] Composite Material Example 8 This composite material embodiment is basically the same as composite material embodiment 1, except that in step S22 of this composite material embodiment, the CVD vapor deposition temperature is 400℃ and the time is 4h.

[0084] Composite Material Example 9 This composite material embodiment is basically the same as composite material embodiment 1, except that in step S22 of this composite material embodiment, the CVD vapor deposition temperature is 300℃ and the time is 8h.

[0085] Composite Material Comparative Example 1 This comparative example provides a composite material, and the preparation method of the composite material includes a ball milling mixing method, specifically including the following steps: Add 10g of the nitrile polymer polyacrylonitrile to 300g of NMP solvent and stir until the polyacrylonitrile is fully dissolved to form a homogeneous slurry; add 1kg of graphite (average particle size D) to a mixing pot. v (50 is 12μm), then the prepared polyacrylonitrile slurry is added to a kneading pot and kneaded at 20 rpm for 2 hours; then it is heated to 80℃ to dry and remove the solvent, obtaining a pre-coated polyacrylonitrile graphite; the pre-coated product and elemental sulfur (S8) powder are added to a planetary ball mill, controlling the mass ratio of S8 to polyacrylonitrile to be 4:1, the ball milling conditions are: rotation speed 300 rpm, ball milling time 4 hours, ball-to-material ratio 10:1, to obtain uniformly mixed fine particles; the ball-milled mixture is loaded into a quartz boat and placed in a tube furnace. Under argon atmosphere protection (argon flow rate 100 mL / min), the temperature is raised to 400℃ at a heating rate of 5℃ / min and held for 6 hours for vulcanization reaction; after the reaction is completed, it is naturally cooled to room temperature under argon protection, and the composite material is discharged.

[0086] Composite Material Comparative Example 2 This comparative example provides a composite material, and the preparation method of the composite material includes spray drying + sintering, specifically including the following steps: 10g of polyacrylonitrile and 40g of elemental sulfur (S8) were weighed and dissolved / dispersed together in 200g of N,N-dimethylformamide (DMF). The mixture was magnetically stirred for 4 h under a water bath heating condition at 60℃ until the polyacrylonitrile was completely dissolved and the elemental sulfur was uniformly dispersed, forming a homogeneous black slurry. The mass ratio of polyacrylonitrile to elemental sulfur was 1:4. The slurry was then fed into a spray dryer using a peristaltic pump. The spray drying conditions were: feed rate 50 mL / min, inlet temperature 180℃, outlet temperature 100℃, and atomizing disc speed 20000 rpm. After atomization, the slurry was instantly dried to obtain spherical precursor particles with a particle size range of 10 μm. The spherical precursor particles obtained by spray drying were loaded into a quartz boat and placed in a tube furnace. Under an argon atmosphere (argon flow rate 100 mL / min), the temperature was increased to 400℃ at a rate of 5℃ / min and held for 6 h to carry out a sulfurization reaction, yielding polyacrylonitrile / elemental sulfur powder. Weigh 10g of polyacrylonitrile / elemental sulfur powder and 100g of graphite (average particle size D). v 50 (12μm) were added together to a high-speed mixer. The mixing conditions were: 500 rpm and 2 hours. After mixing, the material was discharged to obtain the composite material.

[0087] Comparative Example 3 of Composite Materials This comparative example provides a composite material, and the preparation method of the composite material includes a mechanical-physical mixing method, specifically including the following steps: Weigh 10g of polyacrylonitrile and 40g of elemental sulfur (S8), and add them together to a planetary ball mill for ball milling and mixing. The ball milling conditions are: rotation speed 300 rpm, ball milling time 4h, ball-to-material ratio 10:1, to ensure that the polyacrylonitrile and elemental sulfur are thoroughly and uniformly mixed. The ball-milled mixture is then loaded into a quartz boat and placed in a tube furnace. Under an argon atmosphere (argon flow rate 100mL / min), the temperature is raised to 400℃ at a heating rate of 5℃ / min and held at this temperature for 6h to carry out the sulfurization reaction. After the reaction is completed, the mixture is naturally cooled to room temperature under argon protection, and the polyacrylonitrile / elemental sulfur powder is obtained by discharging.

[0088] Weigh 10g of the above-mentioned pre-prepared polyacrylonitrile / elemental sulfur powder and mix it with 100g of graphite (average particle size D). v 50 (12μm) were added together with the material to a high-speed mixer. The mixing conditions were: 500 rpm and 2 hours. After mixing, the material was discharged to obtain the composite material.

[0089] The microstructure of the composite material in Example 1 was observed using scanning electron microscopy. See the attached image for the results. Figure 2 .

[0090] Depend on Figure 2It can be seen that the coating method provided in this application has yielded a uniform and firmly coated sulfur-containing nitrile polymer coating layer.

[0091] The XPS S2p spectra of the coating layer in the composite material of Example 1 were detected by X-ray photoelectron spectroscopy (XPS). The results are shown in [link to relevant documentation]. Figure 3 .

[0092] Depend on Figure 3 It is known that SC bonds are introduced into the coating layer of the composite material prepared in this application, which strengthens the bonding between the coating layer and the graphite particle core.

[0093] Raman spectra of composite materials Examples 1-9 and Comparative Examples 1-3 were measured using a Raman spectrometer, and the ID / IG values ​​were calculated. The test results are shown in Table 1. ID / IG is defined as the intensity ratio of the D peak to the G peak in the Raman spectrum, where the D peak corresponds to structural defects or disordered carbon, while the G peak reflects an ordered graphite lattice. The lower the ID / IG, the higher the degree of graphitization.

[0094] Table 1

[0095] From Table 1, we can obtain: The composite material provided in this application has a lower ID / IG ratio than the composite material in the comparative example, indicating a higher degree of graphitization. This demonstrates that the method of kneading in a solvent avoids damage to the graphite and helps to ensure the structural integrity of the graphite.

[0096] Battery Example 1 This embodiment of the battery provides a battery, and the battery preparation method includes the following steps: The negative electrode includes a copper foil and a negative electrode active material layer disposed on the surface of the copper foil. The negative electrode active material layer includes a negative electrode active material, a negative electrode binder, and a negative electrode conductive agent. The negative electrode active material includes the composite material in Example 1. The negative electrode binder is LA136DL polyacrylic acid binder and carboxymethyl cellulose. The negative electrode conductive agent is conductive carbon black Super-P and single-walled carbon nanotubes (SWCNTs). The mass ratio between the negative electrode active material, LA136DL polyacrylic acid binder, carboxymethyl cellulose, conductive carbon black Super-P, and single-walled carbon nanotubes is 95.45:2:1.5:1:0.05. The negative electrode is assembled into a 450mAh / g soft-pack battery.

[0097] Battery Examples 2-9 Battery Examples 2-9 are basically the same as Battery Example 1, except that the composite material of Composite Material Example 1 is replaced with the composite material of Composite Material Examples 2-9 in Battery Examples 2-9.

[0098] Battery Comparison 1~3 Battery Comparative Examples 1-3 are basically the same as Battery Example 1, except that the composite material of Composite Material Example 1 is replaced with the composite material of Composite Material Comparative Examples 1-3 in Battery Comparative Examples 1-3.

[0099] The specific capacity, rate performance, cycle performance, and high-temperature storage stability of the batteries in Examples 1-9 and Comparative Examples 1-3 were tested; the test results are shown in Table 2.

[0100] The specific capacity test method is as follows: Under a constant temperature environment of 25℃, the test is conducted using a Blue Electric test equipment. The battery is charged and discharged at a current density of 0.1C (1C=300mA / g) and the charge and discharge cycles are repeated twice within a voltage range of 0.005V~2.00V. During the test, the specific capacity of the first charge and the specific capacity of the first discharge of each lithium-ion battery are obtained, as well as the specific capacity of the second discharge of each lithium-ion battery.

[0101] The rate performance test method is as follows: The test is conducted according to the following steps: rest, discharge at 0.1C to 1mV, rest for 10 minutes, discharge at 0.01C constant current to 1mV, rest for 10 minutes, charge at 0.05C constant current to 1.5V, cycle twice, rest for 10 minutes, discharge at 0.1C constant current to 1mV, rest for 10 minutes, discharge at 0.01C constant current to 1mV, rest for 10 minutes, charge at 0.5C constant current to 1.5V, rest for 10 minutes, discharge at 0.1C constant current to 1mV, rest for 10 minutes, discharge at 0.01C constant current to 1mV, rest for 10 minutes, charge at 1C constant current to 1.5V, rest for 10 minutes, and then stop. Record the battery capacity at 0.05C and 1C rates, and calculate the percentage of battery capacity at 1C rate compared to 0.05C rate.

[0102] The test method for cycle performance testing is as follows: Under the test environment of temperature 25℃±5℃, relative humidity 15%~90%, and atmospheric pressure 86Kpa~106Kpa, take 3 soft pack batteries that have completed the voltage drop test and place them in a constant temperature chamber at 25℃. Use the test charge and discharge clamp to clamp the positive and negative terminals of the batteries respectively, and start setting the test steps: (1) rest for 10min; (2) charge at 1C CC / CV to 4.2V, stop at 0.05C; (3) rest for 10min; (4) discharge at 1C CC to 3.0V; (5) cycle (1)~(4) for 1200 cycles; take the capacity retention rate after 700 cycles at 1C.

[0103] The test method for high-temperature storage stability is as follows: the battery is fully charged-fully discharged-fully charged at 0.5C, and the voltage and internal resistance are tested to obtain the initial capacity, voltage and internal resistance data. Then it is stored at 60℃ for 14 days (14d) and 28 days (28d). After storage, the voltage and internal resistance are tested again, and then it is discharged-fully charged-fully discharged at 0.5C to obtain the remaining capacity and calculate the remaining capacity retention rate.

[0104] Table 2

[0105] From Table 2, we can obtain: This application applies vacuum vapor deposition technology to the preparation of graphite coated with sulfur-containing nitrile polymers. It utilizes the molecular diffusion of gaseous sulfur sources to achieve uniform coating, overcoming the fundamental defect of uneven coating in the traditional ball milling method (comparative example 1 of the battery). Furthermore, this application can utilize all sulfur sources as much as possible, thereby improving utilization rate and composite material yield.

[0106] In the preparation method provided in this application, the thickness and sulfur content of the sulfur-containing nitrile polymer coating layer are precisely controlled by precisely controlling the reaction temperature, vacuum degree, and reaction time. Kneading in a liquid solvent avoids the damage to the graphite lattice caused by the mechanical force of ball milling. Simultaneously, in-situ reaction achieves chemical bonding between the sulfur-containing nitrile polymer and graphite. This structural feature contrasts sharply with the physical contact in comparative battery examples 1-2. The chemically bonded interface in this application ensures the stability of the coating layer during long-term cycling, while the continuous and dense coating layer constructs a superior lithium-ion concentration gradient driving system. Furthermore, the uniform and dense coating layer forms a steep concentration gradient after lithiation, which can more effectively drive Li-ion concentration gradients. + The composite material containing thiocyanate compounds coated with graphite diffuses into the graphite interior, achieving a specific capacity exceeding the theoretical capacity of graphite, while significantly suppressing lithium plating behavior at high rates.

[0107] The composite material obtained in this application is used in the negative electrode of the battery, which improves the uniformity, density and tightness of the coating layer, and significantly enhances the battery's specific capacity, rate performance, cycle performance and high-temperature storage stability.

[0108] The technical solutions provided by the embodiments of this application have been described in detail above. Specific examples have been used to illustrate the principles and implementation methods of this application. The description of the above embodiments is only for the purpose of helping to understand the method and core ideas of this application. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of this application. Therefore, the content of this specification should not be construed as a limitation of this application.

Claims

1. A method for preparing a composite material, characterized in that, Includes the following steps: A pre-coating material is provided, the pre-coating material comprising graphite and a nitrile polymer coating the graphite; A sulfur source is provided, and the sulfur is reacted with the pre-coated material via vapor deposition to obtain a composite material.

2. The preparation method according to claim 1, characterized in that, The average particle size D of the graphite v 50 ranges from 4μm to 20μm; The nitrile polymers include polyacrylonitrile, polymethacrylonitrile, polybutene nitrile, polypentene nitrile, polyhexene nitrile, polystyrene-acrylonitrile copolymer, acrylonitrile-butadiene-styrene copolymer, acrylonitrile-butadiene copolymer, hydrogenated acrylonitrile-butadiene rubber, acrylonitrile-styrene-acrylate copolymer, acrylonitrile-chlorinated polyethylene-styrene copolymer, acrylonitrile-methyl methacrylate copolymer, acrylonitrile-acrylate copolymer, acrylonitrile-vinylpyridine copolymer, acrylonitrile-vinyl chloride copolymer, acrylonitrile-vinylidene chloride copolymer, acrylonitrile-maleic anhydride copolymer, and acrylonitrile-acrylamide copolymer. The mass ratio of the graphite to the nitrile polymer is 100:(0.2~3). The average thickness of the pre-coated layer formed by the nitrile polymer coating the graphite is 5 nm to 15 nm.

3. The preparation method according to claim 1, characterized in that, The method for preparing the pre-coated material includes: providing the graphite, the nitrile polymer, and a solvent, mixing and kneading them to obtain the pre-coated material; wherein... The solvent includes one or more of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, N-ethylpyrrolidone, N-cyclohexylpyrrolidone, N-octylpyrrolidone, γ-butyrolactone, propylene carbonate, ethylene carbonate, sulfolane, 1,3-dimethyl-2-imidazolinone, hexamethylphosphoric triamine, tetrahydrofuran, dioxane, acetonitrile, acetone, and methyl ethyl ketone. After the kneading process, the method further includes drying to remove the solvent; the method for drying to remove the solvent includes heating and drying; the temperature for heating and drying is 60℃~100℃.

4. The preparation method according to claim 1, characterized in that, The sulfur source includes one or more of elemental sulfur and metal sulfides, and the metal sulfides include MoS2. x x is any integer from 1 to 5; The mass ratio of the nitrile polymer to the sulfur source is 10:(1~8).

5. The preparation method according to claim 1, characterized in that, The vacuum degree of the vapor deposition is ≤500Pa; The heating rate for the vapor deposition is 1℃ / min to 10℃ / min; The temperature of the vapor deposition is 300℃~600℃; The vapor deposition time is 1h to 8h.

6. The preparation method according to claim 5, characterized in that, The vacuum degree of the vapor deposition is ≤200Pa; The heating rate for the vapor deposition is 2℃ / min to 8℃ / min; The temperature of the vapor deposition is 300℃~400℃; The vapor deposition time is 2h to 4h.

7. The preparation method according to any one of claims 1 to 6, characterized in that, The composite material includes the graphite and a coating layer covering the graphite; wherein, The coating material includes sulfur-containing nitrile polymers; The average thickness of the coating layer is 3nm to 10nm.

8. A composite material, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 7.

9. An electrode, characterized in that, The electrode material includes a composite material prepared by the preparation method according to any one of claims 1 to 7, or includes a composite material according to claim 8.

10. A battery, characterized in that, The battery includes a positive electrode, a negative electrode, a separator, and an electrolyte. The material of the negative electrode includes a composite material prepared by the preparation method according to any one of claims 1 to 7, or includes a composite material according to claim 8, or the negative electrode includes an electrode according to claim 9.